Optimizing University Program Selection: A Comparative Study of Multi-Criteria Methods - Daghouri Ansar; Mansouri Khalifa (E3S Web of Conferences)
This paper aims to present a comparative study of multi-criteria decision-making methods to optimize the selection of university programs. The results of implementing five MCDM methods are compared by evaluating each method using a hierarchical model, which is decomposed into a set of criteria. These criteria include the reputation of the university, the quality of teaching, career prospects, financial costs, the adaptability of the program, and the personal preferences of the student. The results indicate that there are both similarities and differences in the ranking of university programs. This study presents a hierarchical model for evaluating university programs according to the preferences of individual students. It offers an in-depth perspective on the benefits and limitations of each method in the decision-making process.